Evidence that the Allelic Segregation of starch branching enzyme 1 (sbe1) is the Source of a High Amylose QTL in Maize. Issue 1 (1st January 2018) - Gyawali, Abiskar; Auger, Donald
ABSTRACT: 'GEMS‐0067' is a maize ( Zea mays L.) cultivar that is uniquely high in the proportion of amylose endosperm starch relative to amylopectin. We previously identified a significant quantitative trait locus (QTL) for endosperm amylose content on the short arm of chromosome 5 (5S). In that study, both parental lines, GEMS‐0067 and H99ae, were homozygous recessive for amylose extender 1 ( ae1 ), which is located on the long arm of chromosome 5 (5L). The dominant allele encodes starch branching enzyme 2b (SBE2b). Centered within the 5S QTL interval is another starch branching enzyme, starch branching enzyme 1 ( sbe1 ), which also plays a role in the branching of amylopectin. We sought to determine if this QTL is due to allelic segregation of sbe1 or, instead, a closely linked locus. A Mutator ‐induced allele of sbe1 ( sbe1‐Mu ) was employed to address this question. If sbe1‐Mu behaves as a simple recessive allele, it could eliminate the additive nature of the 5S QTL, which would indicate that segregation of the sbe1 alleles present in the original GEMS‐0067 × H99ae hybrid are responsible for the QTL. If not, it would implicate segregation of alleles at a closely linked locus. Pollen possessing sbe1‐Mu was crossed onto a GEMS‐0067 × H99ae hybrid, which separated the high amylose factor from the low amylose factor. A sample of these progeny was grown and self‐pollinated to generate kernels segregating for sbe1‐Mu . Kernels were genotyped for sbe1 alleles and assayed for relative amylose and amylopectin content. Kernels heterozygous or homozygous for the GEMS‐0067 allele of sbe1 had a higher amylose/amylopectin ratio than kernels possessing the H99ae allele. Importantly, sbe1‐Mu behaves as a simple recessive allele regardless of the other sbe1 allele. This implicates allelic variation of sbe1 as being responsible for the high endosperm amylose QTL.